=
Note: Conversion is based on the latest values and formulas.
Factorise? a) x^4+2x^3+3x^2+2x+1 - Socratic x^4+2x^3+3x^2+2x+1=(x^2+x+1)^2. When you have a "symmetric polynomial", one where the coefficients are the same when you read them forwards and backwards, like x^4+2x^3+3x^2+2x+1, then it will have symmetric factors too. Let us assume that the given fourth degree polynomial has a pair of symmetric, quadratic factors. The natural choice, since the …
How do you solve y=2x-1 and y=x+2? - Socratic 5 Aug 2016 · First part of the calculation given in detail so that you can see the method more clearly. The second part uses shortcuts.
How do you find a power series representation for # x^2 / ( 1 23 Apr 2018 · The idea is to relate this expression to the known power series expansion #1/(1-x)=sum_(n=0)^oox^n# Temporarily disregard the #x^2# and consider
How do you graph y = x^2 + 2x + 1? - Socratic 13 Mar 2018 · graph{x^2+2x+1 [-10, 10, -5, 5]} This is a quadratic equation so it makes a Parabola on a graph. Information: x-intercept: (1,0) y-intercept: (0,1) vertex: (1,0) line of symmetry: x=1
How do you factor and solve 2x^2 + x - 1=0? - Socratic 15 Jan 2017 · x=1/2 or x=-1 2x^2+x-1=0 Factorise. 2x^2+2x-x-1=0 2x(x+1)-1(x+1)=0 (2x-1)(x+1)=0 2x-1=0 or x+1=0 x=1/2 or x=-1
How do you integrate #x^2/(x^2+1)#? - Socratic 28 Jun 2016 · x - arctan x + C x^2/(x^2+1) = (x^2+1 - 1)/(x^2+1) = 1 - ( 1)/(x^2+1) int \ 1 - ( 1)/(x^2+1) \ dx = x - color(red)(int \ ( 1)/(x^2+1) \ dx ) in terms of the red bit, use sub x = tan t, dx = sec^2 t \ dt this makes it \int \ ( 1)/(tan^2 t+1) \ sec^2 t \ dt = \int \ ( 1)/(sec^2 t) \ sec^2 t \ dt = \int \ dt = arctan x - C So the full integral is x - arctan x + C
How do you factor x^2-2x+1? - Socratic 25 Jul 2015 · Well 121 = 11*11 = 11^2 and x^2-2x+1 = (x-1)^2, where the coefficients of x-1 - ignoring signs - are 1 and 1. This works with a few other trinomials, like: x^2+6x+9 = (x+3)^2 like 169 = 13^2 It only works if the numbers are small enough, but it can help.
How do you solve x^2-2x-1=x+3? - Socratic 13 Apr 2018 · #x^2-2x-1-x-3=x+3-x-3# Thus, #x^2-2x-1-x-3=0# Add like terms #x^2-3x-4=0# Split middle term so as to ...
How to factor #2x^2+x-1# - Socratic 10 May 2018 · 2x^2+x-1=color(blue)((x+1)(2x-1) Factor: 2x^2+x-1 The method to use is called "splitting the middle term." Multiply the coefficient of the first term by the constant. 2xx(-1)=-2 Find two number that when added equal 1 and when multiplied equal -2. The numbers that meet the criteria are 2 and -1. Rewrite the expression, splitting the middle term x into 2x and -x. 2x^2+2x …
How do you solve y = x^2 + 2x + 1? - Socratic 29 Jun 2015 · To 'solve' y=x^2+2x+1 could mean: 'How do you calculate x for any given y?' y = x^2+2x+1 = (x+1)^2 hence x = -1+-sqrt(y) If y = 0 then x = -1 Here's a little 'trick' to help spot some of these perfect square quadratics... Suppose you have a quadratic: x^2 + 6x + 9 The coefficients of the x^2, x and constant terms are 1, 6, 9 Does the pattern 1, 6, 9 ring a bell? 169 = 13^2 and …